The future of the commons - Meinzen-Dick, Ruth S. (2018)
Ruth Meinzen-Dick POLICY SEMINAR The Future of the Commons Co-organized by IFPRI, the International Association for the Study of the Commons (IASC), and the CGIAR Research Program on Policies, Institutions, and Markets (PIM) OCT 4, 2018 - 12:15 PM TO 01:45 PM EDT